A dimensão teórica e metodológica da catalogação de assunto - Martinho, Noemi Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The Subject Cataloging is a process of thematic representation of the information and was developed in the United States from the consolidation of the american librarianship and of the librarian processes that evidenced the need for further development of catalogs, as they asserted themselves as an instrument indispensable to libraries and their user communities. However, despite Brazil having been heavily influenced by American Library, there is little national literature about and so little discussion of historical, conceptual and methodological aspects of Subject Cataloging. Thus, we addressed these aspects through theoretical study and also the work of Charles A. Cutter, fundamental name to the evolution of Cataloging, and the principles proposed in his Rules for a Dictionary Catalog. Thus, we had by objective was to assist in understanding these fundamentals about Subject Cataloging and provide theoretical support that could contribute to reducing the lack of this theme in Portuguese. From this, we outline the history of the Subject Cataloging departing from its broader context, which is Cataloging as a whole, and the development of American librarianship. Next, we discuss the concept of subject, given its importance and constant presence in the vocabulary of area and in the expression Subject Cataloging. We used the method of Think-aloud protocol, to seek the view of academics and professionals about the discussions raised here and thereby obtain data on the knowledge of these issues in these two spheres of activity, from which we confirm that although these topics have been little space between the Brazilian literature, and so, it is necessary that this approach is carried out to seek of the understanding of this conceptual universe. We conclude so far that actually there is a dearth of literature in Portuguese, to guide the epistemological foundation pillars for the Subject...(Complete abstract click electronic access below)

A Catalogação de Assunto (Subject Cataloging) é um dos processos de representação temática da informação e foi desenvolvida nos Estados Unidos a partir da consolidação da Biblioteconomia estadunidense e dos processos biblioteconômicos que evidenciaram a necessidade de maior desenvolvimento dos catálogos, pois estes se afirmaram como instrumento indispensável às bibliotecas e suas comunidades usuárias. No entanto, a despeito de o Brasil ter sido fortemente influenciado pela Biblioteconomia estadunidense, há pouca literatura nacional a seu respeito e assim, pouca discussão dos aspectos históricos, conceituais e metodológicos da Catalogação de Assunto. Assim, abordamos esses aspectos por meio de estudo teórico e também da obra de Charles A. Cutter, nome fundamental para a evolução da Catalogação, e dos princípios propostos em sua obra Rules for a Dictionary Catalog. Dessa maneira, tivemos por objetivo auxiliar na compreensão desses fundamentos acerca da Catalogação de Assunto e conceder subsídios teóricos que pudessem contribuir para a diminuição da carência desse tema em língua portuguesa. A partir disso, realizamos o percurso histórico da Catalogação de Assunto partindo de seu contexto mais amplo, que é a Catalogação como um todo, e o desenvolvimento da própria biblioteconomia estadunidense. Em seguida, discutimos o conceito de “assunto”, dada a sua importância e constante presença no vocabulário da área e na própria expressão Catalogação de Assunto. Utilizamos o método do Protocolo Verbal em Grupo, para buscar a visão de acadêmicos e profissionais acerca das discussões aqui levantadas e dessa forma, obter dados sobre o conhecimento dessas questões nessas duas esferas de atuação, a partir do que confirmamos que embora tais tópicos tenham tido pouco espaço entre a literatura brasileira, e assim, é necessário que esta abordagem seja...
Keywords: Cutter, Charles Ammi; Catalogação por assunto; Organização da informação; Indexação; Representação temática da informação; Subject cataloging; Charles Ammi Cutter; Organization of information